Batik Motifs for the Distinctive Jarik of the Samin Community in Reinterpreting the Essence of Samin Surosentiko Pitutur Luhur - Wardoyo, Sugeng; Anggorojati, Aryo; Wulandari, Tri (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
The Samin community (Sedulur Sikep) in Margomulyo, Bojonegoro, has the value of Pitutur Luhur inherited by Samin Surosentiko, but it has not been represented in the batik jarik motif as a communal identity. This creation-based research aims to explore this value, realize it in the design of written batik, and examine its philosophical meaning as an effort to preserve intangible cultural heritage. The method used is practice-based research with a qualitative approach through literature study (ethical data), participatory observation, and in-depth interviews with elders (emic data). The creation process refers to the stages of experimentation, manekung, and the formation of the work. The result was in the form of three prototypes of jarik batik written with a dye cover technique with napthol dye (dark blue (wedel), brown (sogan), white), displaying the main motif of Wijaya Kusuma flowers combined with supporting motifs as a representation of the principle of Pitutur Luhur. The three designs (Manunggal Jati, Kamulyan Jati, and Margomulyo) reflect the values of unity, wisdom, and communal harmony. This research contributes to the development of the aesthetics of the archipelago, the enrichment of Indonesian batik motifs, and the strengthening of the visual identity of the Samin people through an adaptive and sustainable approach to cultural preservation.